PENGARUH KOMPENSASI TERHADAP KINERJA TENAGA HARIAN LEPAS-TENAGA BANTU PENYULUH PERTANIAN (THL-TBPP) PADA BADAN PELAKSANA PENYULUH PERTANIAN, PERIKANAN DAN KEHUTANAN KABUPATEN MUSI BANYUASIN - Muhlisin Muhlisin; Ria Novita Restu (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2018)
This study aims to determine the effect of compensation on the performance of Daily Release Workers - Agricultural Extension Workers (THL-TBPP) at the Implementing Agency for Agricultural, Fisheries and Forestry Extension of Musi Banyuasin Regency, South Sumatra. The research was conducted at Agricultural Extension Agency, Fishery and Forestry Agency of Musi Banyuasin Regency with a total sample of 51. The method of analysis used in the research is simple linear regression, by conducting validity test, reliability test and hypothesis test. The results of this study indicate that the compensation has a positive effect on the performance of the Relevant Force-Tenaga Bantu Penuluh Pertanian (THL-TBPP) with a relationship level of 57.8%